Sistem Sistem Informasi Manajemen Surat Berbasis Website di STMIK Pringsewu - ahmad syarifudin; Adi Prasetia Nanda; Sri Hartati (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2021)
Letters are very important in an agency or company. In an agency or company, a good, well-ordered, directed, structured and well-organized letter management is needed. The large number of incoming and outgoing letters at the Pringsewu College of Information and Computer Management (STMIK) and letter management that is still done manually by recording in the agenda book creates problems in document search, so a system that can assist in mail management is needed. With the existence of a mail management information system, it can reduce the difficulties in filing and searching for letters, and improve management. A website-based mail management information system was created using PHP Hypertext Prepocessor (PHP) and MySQL. The result of this research is an information system that can manage incoming and outgoing mail according to the specified flow, and can solve current problems